The Effect of Mother’s Parenting stress on Socio-Emotional Development in Early Childhood (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2023)
Parenting is one of the most important factors in the formation of social emotional development in early childhood. Often the parenting role is borne by the mother and this makes the mother vulnerable to parenting stress. Surabaya is a city with a high density, reaching 8612 people/square kilometer. Based on this, this study aims to determine the effect of parenting stress on mothers in social emotional early childhood in Surabaya City Kindergarten. In this study, the type of research used was ex-post facto, with a purposive sampling technique with a total of 100 respondents, mothers and children aged 5-6 years in Kindergarten in Surabaya City. The analytical method used in this study is a simple linear regression test. Based on the results of the hypothesis testing carried out, it was found that the results of a significance level of 0.000, which is 0.000 <0.05, which means that parenting stress on the mother and social-emotional development meets the criteria for the regression equation. The magnitude of the effect of parenting stress on this mother was tested for the coefficient of determination or R square which had a result of 0.296. This means that the parenting stress variable has an influence of 29.6% on the social-emotional development variable, while 70.4% is influenced by other factors. This means that parenting stress that occurs in mothers can affect how the social-emotional development of children in the future, therefore it is important to manage parenting stress and the school can provide support facilities for mothers and children in the social-emotional development of children and mothers.